A review of the experimental methods used for studying the semantics of proper names - Navrazova, Khava Bakuevna; Makhaev, Mair Ruslanovich; Shamileva, Razeta Daduevna (SHS web of conferences, 2023)
The article describes the experimental methods for studying the semantics of proper names. Conducting experiments is a new trend in the development of modern linguistics due to the development of the anthropocentric paradigm which considers language as a mental phenomenon rather than an independent system (lexicon, grammar). The paradigm goes back to the works by von Humboldt, Steinthal, Potebnya, etc. Native speakers act as subjects in linguistic experiments. Experimental methods are also used in studies of the semantics of proper names. The experimental approach considers this problem in a new light, identifying the semantic components of proper names that are relevant for native speakers, and taking into account ethnic, age, social, gender and temporal aspects. The experimental methods help reveal a new kind of meaning that exists along with the traditional lexical meaning. This is a psycholinguistic meaning that is represented in the minds of native speakers. This allows us to solve one of the most important methodological problems of lexicography of toponymic vocabulary – the search for methods of complex interpretation of the semantics of lexical units, taking into account the mental factor and ways for analyzing language in its close connection with thinking and experience. The article overviews experimental methods for studying the semantics of proper names.